2014
DOI: 10.2308/ogna-51000
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Inter-Fund Transfers to Manage the “Bottom Line” in the Municipal Context

Abstract: This study examines whether municipalities use inter-fund transfers to manage the general fund. Since the general fund is a municipality's largest fund, its financial position often reflects that of the whole municipality. Results indicate that transfers are used to manage the general fund toward zero. In particular, the tendency to use transfers to manage the general fund does not differ between general funds that had a positive and negative pre-managed change in fund balance, suggesting the incentive to repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Dichev and Tang (2008) demonstrated that earnings volatility varied with the volatility of economic shocks. Graham et al (2005) and Felix (2015) showed that CFOs and municipal managers preferred smoothness in earnings and SR, respectively. Erickson et al (2016) provided evidence of differential risk levels in the presence of both earnings and cash flow volatility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Dichev and Tang (2008) demonstrated that earnings volatility varied with the volatility of economic shocks. Graham et al (2005) and Felix (2015) showed that CFOs and municipal managers preferred smoothness in earnings and SR, respectively. Erickson et al (2016) provided evidence of differential risk levels in the presence of both earnings and cash flow volatility.…”
Section: Discussionmentioning
confidence: 99%
“…In the municipal setting, the optimal "earnings" benchmark is at SR equilibrium, or when revenues equal expenditures in the general fund (Apostolou et al, 1985;Apostolou et al, 2014). Municipal managers have an incentive to maintain SR at or near zero, despite a prior surplus or deficit (Felix, 2015). Large surpluses (SR>0) can signal excessive collection of tax revenue or insufficient spending of expenditures for public services (Felix, 2015).…”
Section: Information Content Of Historic Volatility In Earnings and Smentioning
confidence: 99%
See 3 more Smart Citations